Stress, health, and behavior - McCarty, Richard 1947- (New York The Guilford Press, 2023)
"Exposure to stressful life experiences can disrupt key regulatory systems in the body and contribute to a variety of negative health outcomes. This authoritative text takes a biopsychosocial approach to understanding the role of stress in alcohol use disorder, posttraumatic stress disorder, depression, cardiovascular disease, Type 2 diabetes, cancer, and other chronic diseases. It presents cutting-edge knowledge about how stressors are conceptualized and measured; connections to disease processes; systemic racism as a significant, ongoing stressor for people of color; and factors that promote resilience. For each of the disorders discussed, proven and promising stress-targeted clinical interventions are reviewed. Student-friendly features include an end-of-book glossary and an extensive bibliography to facilitate in-depth study of selected topics of interest. "-- Provided by publisher.
"This authoritative text takes a biopsychosocial approach to understanding the role of stress in alcohol use disorder, posttraumatic stress disorder, depression, cardiovascular disease, Type 2 diabetes, cancer, and other chronic diseases. It presents cutting-edge knowledge about how stressors are conceptualized and measured; connections to disease processes; systemic racism as a significant, ongoing stressor; and factors that promote resilience. For each of the disorders discussed, proven and promising stress-targeted clinical interventions are reviewed. Student-friendly features include an end-of-book glossary and an extensive bibliography to facilitate in-depth study of topics of interest"-- Provided by publisher.
Historical aspects of the stress field -- Biological measures of stress -- Behavioral measures of stress -- Stress and alcohol use -- Posttraumatic stress disorder -- Stress and depression -- Stress and cardiovascular disease -- Stress and diabetes -- Stress and the gastrointestinal system -- Stress and cancer -- Stress and infectious diseases -- Systemic racism as a stressor -- Resilience.
Includes bibliographical references (pages 291-327) and index.
Keywords: Psychophysiology; Social psychology; Stress (Physiology); Stress (Psychology)